If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 3(2 + -3x) = 25 8x + (2 * 3 + -3x * 3) = 25 8x + (6 + -9x) = 25 Reorder the terms: 6 + 8x + -9x = 25 Combine like terms: 8x + -9x = -1x 6 + -1x = 25 Solving 6 + -1x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 25 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 25 + -6 -1x = 25 + -6 Combine like terms: 25 + -6 = 19 -1x = 19 Divide each side by '-1'. x = -19 Simplifying x = -19
| 194-2x=43x+19 | | 24x^2+24x=0 | | 27+(4x-30)+(3x-10)+x=360 | | 4(1)-5y=9 | | a^3+7a^2+12a+24= | | 6x^2-9x-105=0 | | 15=200 | | -3x+4y=21 | | -10x+6y=-2(3-y) | | 65-131=11(x-1) | | x-11=-3-20 | | -2x=-6y+9 | | 11x-10x=8x+5 | | x+3=-28+10 | | 4a^2+2.25a+1=0 | | (x+8)(x)(x-2)=96 | | 3x/2+6x/5=5+x/5 | | 5z-z=5-37 | | x-42=48 | | 6v^2-9v-60=0 | | (x+4)(x)(x-2)=96 | | -20x=-10 | | 4x^2-24x+32= | | 2q+b=c | | 12-2x+3x-5-7x= | | 1x=5+0.75x | | 3.5x^7+4.5x^6-2.5x^2+4x=0 | | 42.75=4.75*x | | 75+0.10=400 | | 75+.10=400 | | log(5x+1)+log(2)=Log(9x+10) | | 25.25=1.75*x |